DEIXIS USED IN AVRIL LAVIGNE’S “LOVE SUX“ ALBUM - Faisal, Septian Iman; Wardhani, Dwi Taurina Mila; Amelia, Firqo (ELite Journal : International Journal of Education, Language and Literature, 2023)
There are many deictic words in the lyrics of the songs in Avril Lavigne’s Love Sux album that the listeners must know. This study explains about the kinds of deixis and the meaning of deixis in the song lyrics. This study used descriptive qualitative method in which the researcher described the types and the meaning of deixis in the songs’ lyrics. In collecting the data, the first step was searching the song lyrics, then listening to all songs in the album. The next step was identifying the data and classifying the deixis in song lyrics of Avril Lavigne’s Love Sux album. Then, analyzing the data using theory of deixis by George Yule (1996). The result of study indicated that various deixis such as person dixis, spatial deixis, and temporal deixis were used in song lyrics on the Love Sux album by Avril Lavigne. There were three kinds of person deixis, namely first person, second person, and third person. Person deixis was used to indicte the role of the participants in the song lyrics. Spatial deixis was used to indicate the place or location where the events in the song lyrics. Temporal deixis wass used to indicate the time when an event occured in the song lyrics.